Cinderella's night in Venice - Connelly, Clare (Romance novelist) (Harlequin presents, 2021)
"When Ares Lykaios insists that Bea Jones accompany him to a gala, she wants to refuse--if just to put the arrogant Greek in his place. Yet Ares is as gorgeous as he is commanding, and she can hardly say no to her PR firm's biggest client. Bea is shy, awkward...and breathtaking in a ball gown. And one kiss proves her desire matches Ares's own. So after the opportunity arises to finish what they started in Venice, resisting becomes the ultimate test of his strict self-control!" -- Page [4] cover.